Consultative Meeting on Metadata Clearinghouse and National Geoinformation Infrastructure Networking: A Report - Chhatkuli, Raja Ram; Sigdel, Mahendra Prasad; Paudyal, Dev Raj (Journal on Geoinformatics, Nepal, 2006)
N/A